FINDING THE CONTENTS OF VILLAGE SOLID WASTE (IN INDIA): A TOOL TO DEVELOP A VILLAGE SOLID WASTE TREATMENT PLANT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Background The well connectivity of rural peoples with urban areas, educational awareness and increasing in earning capacity of rural people causes improvement in living standard. These are the main reasons of more solid waste generation in the villages. Any development and change of lifestyle of the urban people attract the rural people leading to generate village solid waste (vsw).Purpose Now it becomes a serious situation in villages also, i.e. Land pollution, Air pollution, and Water pollution due to VSW, hence it is necessary to take action to control this situation. Result This study gives a data of thirty four (34) villages about solid waste. This is in mixed form..Iits analysis means its weight in Kg. In this survey experiment it is observed that maximum plastic, compostable material, ash and garbej materials are present, All VSW material is in mixed form Conclusion This data helps to design various segregation units of waste treatment plant. There is traditional way to collect the waste, no any segregation system is present.